Awareness of benefits and risks of fluoridated toothpaste among IIUM dental and science students - Supa'at, Salwana; Azhar Ariffin, Fatin Nadia; Khairunnizam, Khalis Sabrina; Dewi Ardini, Yunita; Mohd Ibrahim, Mohamad Shafiq (Quantum Academic Publisher Enterprise, 2025)
Dental caries is a significant health issue in Malaysia and globally. Thorough brushing with fluoridated toothpaste can help prevent caries. Although fluoridated toothpaste offers protection against dental caries, its overuse can result in negative effects. Therefore, it is essential to recognise the associated risks and weigh them carefully against its benefits. This study aimed to evaluate the awareness of the benefits and risks of using fluoridated toothpaste and its practice of usage among dental and science students. A cross-sectional survey was conducted using a structured questionnaire comprising three sections: demographic profile, awareness of benefits and risks, and usage of fluoridated toothpaste. A total of 296 students (148 dental and 148 science) participated. Results showed that dental students exhibited a higher level of awareness regarding the benefits of fluoridated toothpaste (95.1%) compared to science students (79.4%). Furthermore, dental students also had greater awareness of the associated risks (58.3%) than science students (33.6%). A statistically significant difference in awareness levels was observed between both groups (p<0.001). Among dental students, awareness increased progressively from Year 1 to Year 4, whereas no significant differences were found across academic years among science students. In conclusion, dental students demonstrated greater awareness of both the benefits and risks of using fluoridated toothpaste than science students. Increased awareness was associated with better oral hygiene practices. Future research could explore targeted interventions to enhance fluoride-related public awareness and promote effective oral health behaviours